The level of employer awareness towards social security organization in Kuala Pilah / Muhamad Kairul Ramlos - Ramlos, Muhamad Kairul (Faculty of Business and Management, 2010)
The main purpose of this research is to measure the level of employer awareness towards SOCSO in Kuala Pilah. As information, SOCSO is a Government Department to implement, administer and enforce the Employees’ Social Security Act 1969 and The Employees’ Social Security (General) Regulations, 1971. SOCSO schemes are to guarantee the payment of cash benefits to the employee and his/her dependents should any unforeseen events occur.